A rare Philippine plant found again after almost a century: the rediscovery and lectotypification of Acranthera philippinensis (Rubiaceae) - Ordas, Jorge Anton D.; Zamudio, Sarah Grace S.; Docot, Rudolph Valentino A. (Phytotaxa, 2023)
A floristic excursion in Zamboanga del Sur, Philippines led to the rediscovery of Acranthera philippinensis, an endemic Rubiaceous taxon with very limited information since 1905. This study provided a detailed description, a color plate, a distribution map of A. philippinensis, and information on its habitat and phenology. Based on the IUCN guidelines, A. philippinensis is provisionally categorized as Endangered (EN). In addition, a lectotype is also designated for this name. The findings of this study demonstrate the urgent need for more botanical research to be conducted in the Philippines, where numerous species await recollection and discovery.